Reviving the Ganges water machine: accelerating surface water and groundwater interactions in the Ramganga sub-basin - Surinaidu, L.; Muthuwatta, Lal P.; Amarasinghe, Upali A.; Jain, S.K.; Kumar, S.; Singh, S. (Elsevier, 2016)
Reviving the Ganges Water Machine (GWM), coined 40 years ago, is the most opportune solution for mitigating the impacts of recurrent droughts and floods in the Ganges River Basin in South Asia. GWM create subsurface storage (SSS) by pumping more groundwater from the aquifers before the monsoon for irrigation and other uses and recharge it during the monsoon. The present study uses fully processed and physically based numerical models, MODFLOW and SWAT, in a semi-coupled modelling framework to examine the technical feasibility of recharging the SSS. The aquifer was simulated as a two-layer system using hydrogeological and groundwater data, model was calibrated from 1999 to 2005 and validated from 2006 to 2010. It assesses the impacts of gradual increase of SSS in 10 years from the base year 2010 under two scenarios (increased rainfall or controlled pumping and recharge) to meet a potential unmet demand of 1.68 billion cubic meters (Bm3) in the Ramganga sub-basin with an area of 18,668 km2. The results show that 3–4 m of subsurface storage can be created by groundwater pumping of 0.25 Bm3/year by 2020. Under the controlled pumping and recharge scenario, groundwater recharge and river seepage could increase by 14% (4.21–4.80 Bm3) and 31% (1.10–1.44 Bm3), respectively. However, baseflow will decrease by 30% (0.18–0.12 Bm3) over the same time period. The results also show that recharge increased 44% (4.21–6.05 Bm3) under an increased rainfall scenario. Simultaneously, river seepage and baseflows would increase 36% (1.10–1.14 Bm3) and 11% (0.18–0.20 Bm3), respectively. A well-designed managed aquifer recharge program is required to eliminate the negative impact of river flows in the low flow season.